Dynamic AIE crosslinks in liquid crystal networks: visualizing for actuation‐guiding, re‐bonding for actuation‐altering. (5th October 2022) - Jiang, Zhi‐Chao; Xiao, Yao‐Yu; Hou, Jun‐Bo; Chen, Xin‐Shi; Yang, Ni; Zeng, Hongbo; Zhao, Yue
Abstract: Covalent adaptable liquid crystal networks (CALCNs) are highly potential actuating materials due to their actuation properties and shape reprogrammability. Given the importance of network crosslinking state in a CALCN actuator, we sought an all‐in‐one strategy to probe and visualize its dynamic network while ensuring actuation and reprogramming. Here, tetraphenylethylene derivatives were incorporated into liquid crystal networks via the Diels–Alder (DA) reaction, acting simultaneously as reversible crosslinkers and aggregation‐induced emission (AIE) fluorescent probes. The thermally tunable fluorescence of the resulting network can correlate to and thus visualize the actuator's crosslinking status, actuation capability and temperature in real‐time and in situ, yielding an intriguing actuation limit‐alerting function. Furthermore, we verified unprecedented reprogrammability of the AIE‐type CALCNs through both associative and dissociative exchange mechanisms of DA chemistry. Abstract : Novel covalent adaptable liquid crystal network (CALCN) actuators crosslinked by dynamic AIE luminogens were built based on Diels–Alder chemistry. This all‐in‐one material design "visualizes", through fluorescing, the crosslinking state and actuation capability for actuation‐guiding in CALCN, while enabling network "re‐bonding" through associative and dissociative exchange mechanisms for unprecedented actuation‐reprogrammability.